Determinants of fertility differentials in Uganda based on the Ugand a demographic and health survey 1988/89 - Otim, Esunget Stephen (Kampala : Makerere University, 1994)
Thesis (M.A) Demography - Makerere University, 1994.
Includes bibliographical references (p. 122-127).
Keywords: Fertility, Human -- Uganda